2012
DOI: 10.1159/000337490
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Platelet-Rich Plasma and VEGF-Transfected Mesenchymal Stem Cells on Vascularization and Bone Formation in a Critical-Size Bone Defect

Abstract: Both platelet-rich plasma (PRP) and vascular endothelial growth factor (VEGF) can promote regeneration. The aim of this study was to compare the effects of these two elements on bone formation and vascularization in combination with bone marrow stromal cells (BMSC) in a critical-size bone defect in rabbits. The critical-size defects of the radius were filled with: (1) a calcium-deficient hydroxyapatite (CDHA) scaffold + phVEGF<sub>165</sub>-transfected BMSC (VEGF group), (2) CDHA and PRP, or (3) CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 127 publications
3
45
1
Order By: Relevance
“…Similar results were reported in the double Ang-1/BMP-2 and VEGF/BMP-2-overexpressing BM-MSCs [47, [116][117][118]. However, BM-MSCs engineered to exclusively overexpress the pro-angiogenic VEGF gene were found to be strong inducers of new bone formation by the promotion of new vessel formation among the scaffolds used as templates [119,120]. Curiously, BMMSCs were converted into bone tissue after the overexpression of the Epo gene [121].…”
Section: Bone Formation Attempts Using Mscssupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results were reported in the double Ang-1/BMP-2 and VEGF/BMP-2-overexpressing BM-MSCs [47, [116][117][118]. However, BM-MSCs engineered to exclusively overexpress the pro-angiogenic VEGF gene were found to be strong inducers of new bone formation by the promotion of new vessel formation among the scaffolds used as templates [119,120]. Curiously, BMMSCs were converted into bone tissue after the overexpression of the Epo gene [121].…”
Section: Bone Formation Attempts Using Mscssupporting
confidence: 75%
“…GDF-5 [102][103][104] TIMP-1 [106] Bcl-2 [101] BONE FORMATION BMP-2 [86][109-111] BMP-2/SDF-1ÎČ [113] BMP-2/HIF-1α [114] BMP-2/Ang-1 [47] BMP-2/VEGF [116][117][118] BMP-2/miR-148b [142] BMP-4/-6/-7 [125,126] VEGF [119,120] Epo [121] IGF-I [128,129] OGP [127] Leptin [130] PDGF [131] ephrinB2 [132] ITGA2 [133] NELL1 [134] ÎČ-catenin [135] HI Cb TA Fo Na LIVER REGENERATION VEGF [144] ATP7B [155] HN HN…”
Section: Cartilage Productionmentioning
confidence: 99%
“…Rabbit: [218] (bFGF-rbMPC), [149] (rbMPC/ferumoxide), [219] (hAng1-rbMPCs/PRP), [220] (hVEGF-rbMPC/PRP) Minipig: [221] (hBMP2/hVEGF-pADMPC), [222] (US2/US3-pADMPC)…”
Section: Animal Models In Cell-based Therapiesmentioning
confidence: 99%
“…Using the terms [(bmac OR bone marrow aspirate concentrate OR bmc OR bone marrow concentrate, OR mesenchymal stem cells) AND (bone OR osteogenesis OR fracture healing OR nonunion, OR delayed union)] we searched the PubMed/MEDLINE and the EMBASE electronic database in July [14][15][16][17][18][19][20][21][22][23][24][25]2014. The reference lists of included studies were also reviewed and compared with the collected studies to ensure no pertinent articles were omitted.…”
Section: Literature Searchmentioning
confidence: 99%
“…Eight studies (23%) reported cluster of differentiation (CD) markers. [17][18][19][20][21][22][23][24] Three studies (8%) analyzed for growth factors, which primarily focused on vascular endothelial growth factor (VEGF). 19,20,23 …”
Section: Evaluation Of Bmac Preparationmentioning
confidence: 99%